A New Topology of the Human Y Chromosome Haplogroup E1b1 (E-P2) Revealed through the Use of Newly Characterized Binary Polymorphisms - Trombetta, Beniamino; Cruciani, Fulvio; Sellitto, Daniele; Scozzari, Rosaria (PLOS ONE, 2011)
Haplogroup E1b1, defined by the marker P2, is the most represented human Y chromosome haplogroup in Africa. A phylogenetic tree showing the internal structure of this haplogroup was published in 2008. A high degree of internal diversity characterizes this haplogroup, as well as the presence of a set of chromosomes undefined on the basis of a derived character. Here we make an effort to update the phylogeny of this highly diverse haplogroup by including seven mutations which have been newly discovered by direct resequencing. We also try to incorporate five previously-described markers which were not, however, reported in the 2008 tree. Additionally, during the process of mapping, we found that two previously reported SNPs required a new position on the tree. There are three key changes compared to the 2008 phylogeny. Firstly, haplogroup E-M2 (former E1b1a) and haplogroup E-M329 (former E1b1c) are now united by the mutations V38 and V100, reducing the number of E1b1 basal branches to two. The new topology of the tree has important implications concerning the origin of haplogroup E1b1. Secondly, within E1b1b1 (E-M35), two haplogroups (E-V68 and E-V257) show similar phylogenetic and geographic structure, pointing to a genetic bridge between southern European and northern African Y chromosomes. Thirdly, most of the E1b1b1* (E-M35*) paragroup chromosomes are now marked by defining mutations, thus increasing the discriminative power of the haplogroup for use in human evolution and forensics.